Design and development of wireless RFID reader communication system at UHF band - Razalli, Mohammad Shahrazel; Ahmat Raslan, Sharuzzaman; Shafie, Siti Mariam; Mahdi, Mohd Adzir (2005)
In this paper, the proposed communication between the RFID reader and computer host is by using wireless and the communication is set to RS232 protocol. The system is operated at UHF band (378 MHz) and it uses an amplitude shift keyed modulation technique. The system is established by modulating the amplitude of the high bit or bit ‘1’ of the signal at radio frequency wave at the UHF carrier wave. For the low bit or bit ‘0’ there is no RF modulation taken place at the transmitter circuit, therefore the receiver receives a low input and defines it as the bit ‘0’. This RFID wireless reader communication system can guarantee a good communication range in between 20 to 30 meters line of sight or without line of sight. It is very useful for the outdoor such as tree tagging and electronic gardening applications.